(untitled) (Collection of research papers «PROGRESSIVE TECHNIQUE AND TECHNOLOGIES OF FOOD PRODUCTION ENTERPRISES, CATERING BUSINESS AND TRADE», 2025)
The results of the analysis of the physical and mechanical properties of millet seeds and seeds of littering the heap after its collection are presented. It was found that most littering can be separated on seed cleaning machines, which are equipped with sieves with rectangular and round holes, but chickweed and mouseweed seeds can be separated only partially, so the results of the research are undoubtedly relevant. For cleaning the heap, general-purpose separators with pneumatic-sieve-trier working bodies are mainly used. Most littering and impurities that differ from millet seeds in size and aerodynamic properties are separated on such separators, but the seeds of difficult-to-separate weeds chickweed and mouseweed are close in size and aerodynamic properties to millet seeds. Therefore, it is impossible to separate them on these machines without significant costs of the main crop as waste. The purpose of the study is to determine the rational parameters of the process of separation of millet seeds on a gravitational friction separator using active planning of the experiment and conducting a graph-analytical analysis of the results obtained. Materials and methods of research. The article applies theoretical and computational-experimental methods based on the provisions of mathematical statistics, using the Compass 3D and MathCad program packages and the methodology for planning a multifactor experiment with conducting a graph-analytical analysis. Millet seeds of the 2023 harvest littered with weed seeds were taken as the material. To clean the millet heap from difficult-to-separate impurities, a simple design of a friction separator with a mixture feed perpendicularly inclined separating deck installed at an angle to the horizon by an inclined feeder. The results of experimental studies of the influence of the angles of inclination of the deck and feeder, as well as the material supply on the output of purified fractions of the friction separator of millet seeds, are presented, and the rational parameters of its operation are determined using active planning of a multifactor experiment, which is noted in the conclusions of the work.